Effects of Intranasal Oxytocin Administration on Sexual Functions in Healthy Women: A Laboratory Paradigm. Issue 3 (June 2018) - Kruger, Tillmann H.C.; Deiter, Frank; Zhang, Yuanyuan; Jung, Stefanie; Schippert, Cordula; Kahl, Kai G.; Heinrichs, Markus; Schedlowski, Manfred; Hartmann, Uwe
Abstract: Purpose: The neuropeptide oxytocin (OXT) has a variety of physiological functions in maternal behavior and attachment including sexual behavior. Based on animal research and our previous human studies, we set out to investigate intranasal administration of OXT and hypothesized that OXT should be able to modulate sexual function in women. Methods: In a double-blind, placebo-controlled, crossover laboratory setting, the acute effects of intranasal administered OXT (24 international units) on sexual drive, arousal, orgasm, and refractory aspects of sexual behavior were analyzed in 27 healthy females (mean age ± SD, 27.52 ± 8.04) together with physiological parameters using vaginal photoplethysmography. Findings: Oxytocin administration showed no effect on subjective sexual parameters (eg, postorgasmic tension; P = 0.051). Physiological parameters (vaginal photoplethysmography amplitude and vaginal blood volume) showed a response pattern towards sexual arousal but were not affected by OXT. Implications: Using a well-established laboratory paradigm, we did not find that intranasal OXT influences female sexual parameters. Also, sexual drive and other functions were not affected by OXT. These findings indicate that OXT is not able to significantly increase subjective and objective parameters of sexual function in a setting with high internal validity; however, this might be different in a more naturalistic setting. Abstract : Supplemental digital content is available in the text.